ANALISIS PREFERENSI KONSUMEN TERHADAP PRODUK OLAHAN MANGGA - Nurisa Asrienda Shafira; Elly Rasmikayati; Bobby Rachmat Saefudin (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The production of mangoes in Indonesia, which is seasonal, causes mango production to be abundant during the harvest season and scarce when it is outside the harvest season. Currently, there are many alternatives in processing mangoes into processed products so that consumers can continue to consume mangoes outside the harvest season. However, it is not known what kind of mango processed products that are suitable for consumer preferences. This study aims to describe the characteristics of consumers of mango processed products and consumer preferences for processed mango products. The method used in this research is descriptive statistics and conjoint analysis. The results showed that consumers of processed mango products were dominated by women aged 21 years with an allowance of IDR 500.000 - IDR 1,000,000 per month and live in Java. Consumer preference for processed mango products refers to the choice of mango puree products with a sour taste and low price (less than IDR 15,000) The order of product attributes that are important to consumers is price (46%), type of product (41%), and taste (13%).